Analisis Pengelolaan Desa Ekowisata di Kabupaten Ogan Ilir (Studi Kasus Kampung Warna Warni Burai) - Patrysya, Chelina Putri; Widodo, Slamet; Alamsyah, Alamsyah (Jurnal Ilmiah Pariwisata; Vol 29 No 1 (2024): Jurnal Ilmiah Pariwisata, 2024)
Warna Warni Burai Village is a water tourism village or marine tourism, besides that Burai Village also has many craft and culinary tours in it. However, in its management, Burai Village still has several problems ranging from tourist facilities, accommodation, and so on. This research was conducted by the author to know the causes of problems that exist in the management in Burai Village. This research is descriptive qualitative research using primary data and secondary data. In this study, the method of the bottom-up approach was used and based on the theory of tourism management from Andi Mappi Sammeng. Data collection techniques used in this study were observation techniques, in-depth interviews conducted with several key informants and non-key informants, and documentation techniques carried out at the Youth, Sports, and Tourism Office of Ogan Ilir Regency. For the analysis of this study using the triangulation method from the results of observations, interviews, and documentation that have been obtained by researchers. Standard operating procedures for Tourism Village Guidelines in its management. In addition, tourism product marketing is also needed to increase rural Micro, Small, and Medium Enterprises. Tourism promotion needs to be improved again, not only through social media, and requires an attractive schedule and promotional content. Keywords: management, tourism village, Burai Color Village, Youth, Sports, Dinas Pemuda Olahraga d an Pariwisata